Management Leadership Styles and their impact on the motivation of staff of the third sector - Silva, Maria do Carmo (2014)
Leadership and motivation are key aspects in achieving the success of organizations. Leaders have a prominent role in organizations, either through strategic decision-making, both in motivating associates. The central objective of this study is to know the styles of leadership and motivation dominant in the third sector. Therefore, we want to know which has the characteristics of the current leaders and effective leaders, existing types of motivation, and the relationship established between the current leadership and motivation in the nonprofit sector. We conducted a study of character quantitative, exploratory and correlational, using as an instrument of data collection, a questionnaire, to assess motivation and leadership in the hospitality industry. As main conclusions obtained that the characteristics are different from the current leader of the characteristics of effective leaders and the motivations depending on several factors may be intrinsic or extrinsic. Regarding work motivation, this is significantly correlated with the generality of the items of the current leadership, however, the characteristics of the current leader does not show significant correlation with the leader's role in motivating the respondents.